# Algebra

posted by .

x-2y=.9
4x-3y=13.1

Solve using the substitution method.

• Algebra -

Well first you change x - 2y = .9 to x = .9 + 2y, by adding y from both sides of the equation.

Then, you substitute x=.9 + 27 into 4x - 3y = 13.1 to get 4(.9 + 2y)- 3y= 13.1. Use the distrubutive property and you get 4 * .9 = 3.6 and 4 * 2y = 8y.

Now you have 3.6 + 8y - 3y = 13.1. Simplify to get 3.6 + 5y = 13.1, since 8y - 3y = 5y.

So you subtract 3.6 from both sides to get 5y = 9.5. Divide this by -9 on both sides to get y = 1.9

Plug this in to one of the equations: x - 2y = .9 to get x - 2(1.9) = .9.
You get x - 3.8 = .9. Add 3.8 to both sides to get x=4.7.

The answer is (4.7 , 1.9)

## Similar Questions

1. ### Substitution Method-Plz help

Use the Substitution method to solve the system of equations. x + y = -4 x - y = 2 solve for x in the second equation. x= y+2 Put that in for x in the first equation: x+y=-4 (y+2) + y = -4 solve for y. Then, x= y+2 i don't get it.How …
2. ### algebra

using the substitution method how do you solve y=-1/3x y+2x=5
3. ### algebra

Solve using the substitution method 6x-3y=18, 6x+3y=-12
4. ### Algebra

Solve using the substitution method. 0.3x+0.2y=5,0.5x+0.4y=11
5. ### Algebra

4x+y=42 6x-5y=50 Solve using the substitution method.
6. ### Algebra

Solve using substitution method 3x+8y=20 x=24-7y
7. ### Algebra 1

bobpursey, In this problem you helped me with earlier: Solve using any appropriate method. y = 2× - 5, y = ½× + 1 Substitution, substitute for y. 2×-5=½ × + 1 3/2 x=6 x=4 y= 2*4-5=3 How did you choose which method you were going …
8. ### Algebra Help!!

solve using the substitution method. y= 5 - 3x 4x + y= 7
9. ### Algebra

If 2x + 2y = 20 & 5x - 3y = 15 Solve using the substitution method.
10. ### Algebra

solve using substitution method: 4x+5y=21 x=48-6y

More Similar Questions